Design of a sub-1V CMOS reference voltage generator. (September 2019) - Tsitouras, Athanasios; Sotiriadis, Paul P.
Abstract: In this paper a low complexity, sub-1V, reference voltage generator with low voltage sensitivity over PVT variation and high power supply rejection ratio (PSRR) is proposed. It consists of a traditional bandgap reference core where resistors are used for generating both the PTAT and CTAT currents, which are then added forming a temperature-independent current. A new 1 V modified folded cascode operational amplifier is proposed and used in the main bandgap's loop resulting in low offset, high loop gain and adequate loop phase margin of 58.9°. The loop consists of only two inverting stages and the circuit can be integrated entirely without the need of external large capacitors for frequency compensation. A regulated cascode current source is employed for accurately mirroring of the core temperature-independent current to a resistive load, where the reference voltage is generated. The proposed circuit was simulated in SPECTRE achieving an output reference voltage variation of 3.62%, without trimming, over process variation corners with ±10% variation of the 1 V power supply voltage and within the industrial temperature range, from −40 °C to 125 °C. The temperature coefficient from −40 °C to 125 °C is 6.81 ppm/°C at 1 V at the typical process corner. The PSRR at 1 Hz and the output RMS noise within a bandwidth of 100 MHz are −69.85 dB and 279 μV RMS, respectively, at the typical process corner, at a supply voltage of 1 V and temperature of 27 °C. Typical power consumption is 452 μA at 1 V.